Kualitas Pelayanan Program Jemput Bola Terpadu Oleh Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sidoarjo - Reza Marfiati; Oktarizka Reviandani (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
The state's efforts to meet the basic needs of its citizens are through public services. Where the position of state officials as service providers must be oriented towards optimal service and community satisfaction is a priority. One of the efforts made by Dispendukcapil district. Sidoarjo, namely through the Integrated Pick Up Football program. Integrated Ball Pick-up is a population administration service that is carried out by visiting the location you want to go to. This program aims to encourage regional innovation in providing services, especially for communities who are constrained by distance in managing population administration. This research aims to determine the quality of service from the Integrated Ball Pick-up program implemented by the Sidoarjo Regency Population and Civil Registration Service. The results of this research show that the quality of service from the Integrated Pick-up and Ball program is quite good and effective in helping the community to manage population administration. Based on the Tangible dimension, it proves that people feel the service is easy and effective, the Reability dimension proves that the service provided is swift and efficient, the responsiveness dimension proves the responsiveness of officers in solving community problems, the assurance dimension proves a guarantee of the authenticity and security of community population data, and the empathy dimension proves The existence of a community satisfaction survey provides the community with the opportunity to provide an explanation of the performance of officers in providing services so that good communication can be established between officers and the community.